Comparison of Mean Operative Time in Patients Undergoing Ho:YAG Laser Lithotripsy and Pneumatic Lithotripsy in Ureterorenoscopy for Ureteric Calculus (Medical Forum Monthly, 2024)
Objectives: To compare the mean operative time in patients undergoing Ho:YAG laser lithotripsy and pneumatic lithotripsy for ureteric stones.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Armed Forces Institute of Urology, Rawalpindi from August 2015 to 12 February 2016.Materials and Methods: The study included 60 patients requiring ureteroscopic lithotripsy for treatment of ureteric calculi. Patients were divided into Ho:YAG lithotripsy group (30) and pneumatic lithotripsy group (30). The operative time in minutes was calculated in all patients from initial cystoscopy till ending of ureteroscopy after the stone fragmentation into small particles. All the information was recorded on a specially designed questionnaire.Results: The mean age and SD of all patients was 36.90±12.11. The male to female ratio was 49:11. The baseline demographic variables; mean age, gender, side of stone and location of stone were found similar between the two groups (p>0.05). The type of intra-ureteral lithotripsy was found a significant predictor of mean operative time taken for the procedure. The average operative time taken for Pneumatic lithotripsy procedure increased by 9.13 minutes as compared to the Ho: YAG laser lithotripsy procedure (R2=0.33, p<0.001). The mean operative time was not found significantly different between males and females; age groups; sides of stones and different locations of stones, as a whole, as well as in both groups separately (p>0.05).Conclusion: It is speculated that the Ho:YAG laser lithotripsy is a better procedure compared to the Pneumatic lithotripsy, in terms of the operative time required for the procedure.